Factors Associated with Providing the Basic Immunization to Infants - Iskandar Arfan; Mardjan Mardjan; Yulsi Testiani (JURNAL INFO KESEHATAN, 2021)
Basic immunization is the first providing immunization to acquire the immune level on the verge of protection given to baby before one year which was aimed to get a full set of basic immunization for each baby with a good indicator that is full immunization (IDL). The indicator was influenced by several independent variables such as mother’s job status, education, knowledge, attitude, perception, and support from cadre and family. From total 89 villages in Lamandau district since 2015 to 2018, there were 82 villages of Universal Child Immunization (UCI) (92.1%) increased by 22.78% than 2016 is 69.32%. However, there was Drop Out (DO) of 2.83% from the village thathad not reached a full set of basic immunization of infants in Kujan Village. The objective of this study is to determine the factors associated with providing a full set of basic immunization of infants in Kujan village, Bulik district, Lamandau Regency, Central Kalimantan Province. The research employed cross sectional design. Data was collected from 80 mothers who had children aged 12-24 months during February 2020. The study samples was conducted with total sampling (80 respondents). The results of study used chi square test with levels of trust that is 95%. It showed a significant relationship between education by providing a full set of basic immunization of infants with p-value = 0.000. Meanwhile, employment status, knowledge, attitudes, family support, perceptions, support from cadres were not related to complete immunization. Therefore, based on the results of this study, it is suggested to the Lamandau Regency Government in the long term to improve the education of healthy mothers and also massive education related to the importance of immunization to increase the complete basic immunization coverage in Kujan Village.